Comorbidity of esophageal achalasia, mixed anxiety and depressive reaction in a young female patient: problems of diagnosis and treatment - N.. P. Garganeeva; M. F. Belokrylova; A. K. Kostin; A. P. Koshel; E. M. Epanchintseva; V. F. Lebedeva; M. M. Aksenov; O. E. Perchatkina; I. G. Kartashova; V. A. Rudnitsky; Yu. N. Gorbatsevich; E. V. Tsybulskaya; et al. (Бюллетень сибирской медицины, 2019)
Achalasia cardia (“cardiospasm”, “phrenospasm”, “dolichoesophagus”, “megaesophagus”, “stenosis of cardia”) represents a primary impairment of esophageal motor function associated with impaired lower esophageal sphincter relaxation and peristalsis defects of the thoracic esophagus. It is diagnosed at the age of 25 to 60 years, making up to 20% of all diseases of the esophagus, and is characterized by a triad of symptoms: dysphagia, regurgitation and chest pain when swallowing. In most cases the first manifestations of achalasia are preceded by stress situations in the anamnesis that complicates the differential diagnosis of psychogenic esophageal spasm. The presented clinical case illustrates difficulties of early diagnosis of achalasia cardia in a young femalepatient with severe anxiety and depressive symptoms which develop under conditions of chronic stressful situations in the family or at work. The issues of interdisciplinary interaction of health professionals (physician, gastroenterologist, psychiatrist, psychotherapist, and surgeon) on the course of examination and management of patients with comorbid physical and mental pathology are discussed. The efficiency of the integrative approach to treatment and rehabilitation with the use of modern reconstructive surgical interventions as well as conservative methods of therapy, psychopharmacotherapy and personality-oriented psychotherapy proves the relevance of studying psychosomatic aspects of achalasia cardia.